(untitled) (International Journal of Engineering and Computer Science, 2017)
Brain Computer Interface(BCI) has provided a direct medium of communication between human beings and external devices. It is a boon for people with severe motor disorders as it provides means of control and communication for them. Recently more efforts on out of the lab BCI based research with the help of Electroencephalogram (EEG) signals from brain has provided many applications. In this technology, specific features of brain activity are considered and transformed into device control actions. This kind of interface would help disabled individuals to become independent thus improving their quality of life